2013
DOI: 10.1088/0963-0252/22/4/045014
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the stable ‘quasi-periodic’ glow regime of a nanosecond repetitively pulsed discharge in air at atmospheric pressure

Abstract: This paper presents simulations of the dynamics of nanosecond repetitively pulsed discharges between two point electrodes in atmospheric pressure air at 300 and 1000 K. At 300 K, the preionization left by successive discharges at the end of interpulses mainly consists of positive and negative ions with a density of about 10 9 cm −3 for a repetition frequency of 10 kHz. When photoionization is taken into account with a level of seed charges of about 10 9 cm −3 , the dynamics and the characteristics of the disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 24 publications
6
57
0
Order By: Relevance
“…Nagaraja et al [80] developed an integrated theoretical and numerical framework and provided temporal evolution and dynamics of chemical kinetics, energy coupling, gas heating, and generation of active particles excited by long‐term repetitive pulses in low‐pressure air ( t pw : 3 ns, PRF: 1–100 kHz, consecutive pulse number: up to 100 pulses). Tholin and Bourdon [22, 23, 81, 82] systematically simulated external factors on the development of repetitively pulsed nanosecond discharges ( t pw : 12 ns, PRF: 1 Hz–100 kHz, consecutive pulse number: up to 7 pulses), including the background gas temperature, hydrodynamics expansion, and external circuit impedance. As illustrated in Fig.…”
Section: Discharge Mode Transition In the Repetitively Pulsed Dischmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagaraja et al [80] developed an integrated theoretical and numerical framework and provided temporal evolution and dynamics of chemical kinetics, energy coupling, gas heating, and generation of active particles excited by long‐term repetitive pulses in low‐pressure air ( t pw : 3 ns, PRF: 1–100 kHz, consecutive pulse number: up to 100 pulses). Tholin and Bourdon [22, 23, 81, 82] systematically simulated external factors on the development of repetitively pulsed nanosecond discharges ( t pw : 12 ns, PRF: 1 Hz–100 kHz, consecutive pulse number: up to 7 pulses), including the background gas temperature, hydrodynamics expansion, and external circuit impedance. As illustrated in Fig.…”
Section: Discharge Mode Transition In the Repetitively Pulsed Dischmentioning
confidence: 99%
“…Progressive breakdown/flashover mechanisms under long‐term repetitive pulses have not been fully revealed, specifically why the initial corona discharge eventually triggers catastrophic breakdown/flashover in the pre‐breakdown stage and what the insulation thresholds are at a long‐term operation. Despite the fact that the progressive ‘corona–glow–spark’ transition is frequently observed under long‐term repetitive pulses [16, 2224], a reversed transition from the spark to diffusive discharge has been reported [25]. The real‐time tracking and actively confining desired discharge modes are technically challenging, especially the temporal integration of complex memory effects in the long‐term operation and the bounds of discharge instabilities are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, streamers play an essential role in natural discharges, since they pave the path for lightning and sprites. They have been studied in different gases and in different electric field configurations both experimentally [8,9,10,11,12,13,14] and numerically [15,16,17,18,19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the electrical dynamics during a burst of nanosecond discharge pulses may exhibit periodic behaviours for low flow velocities and in the absence of significant variations in the gas number density or mixture composition. Tholin et al [14] observed similar behaviour in their 2D simulations of pulsed nanosecond discharges in a pin-pin geometry at 1 atm pressure. The plasma reached a 'quasi-periodic' glow regime with repetitive application of voltage waveforms.…”
Section: Introductionmentioning
confidence: 54%
“…High-fidelity NRPD simulations can be immensely beneficial in understanding the complex electric-field dynamics and in quantifying the key kinetic pathways for active species production and their ensuing chemical reactions. There have been significant efforts in developing self-consistent models of nanosecond discharges for various applications [5,6,[11][12][13][14]. In this context, self-consistency refers to the numerical solution of the coupled system of equations for the electric potential, charged and neutral species continuity and flow dynamics, without any adjustable parameters.…”
Section: Introductionmentioning
confidence: 99%